Guaranteed income as a replacement for the welfare state - Murray, C (Foundation for Law, Justice and Society, 2008)
A guaranteed income (GI) that replaces the welfare state is not currently on the political agenda, but it offers the possibility for a grand compromise that could attract a majority political coalition: for the Left, it represents larger government in that it constitutes a state-driven redistribution of wealth, while for the Right, it offers smaller government in terms of the state’s power to control people’s lives. The overarching reason to scrap the apparatus of the welfare state is that the welfare state is self-destructing. After a process that has taken decades, the welfare state has severely degraded the traditions of work, thrift, and neighbourliness which enabled the system to work at the outset. It is now spawning social and economic problems that it is powerless to solve. The proposed GI may be expected to bring about a substantial reduction in extramarital births, and to increase, to an uncertain extent, labour force participation among young males currently outside of the labour force.